(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
The article is devoted to the beginnings and religious practice of the Sufi Nāṣiriyya brotherhood, a branch of Šāḏiliyya. The brotherhood was established in the 17th century in southern Morocco, and its main religious and intellectual center from the very beginning was the town of Tāmkrūt, where a zāwiya still exists today with its famous library of manuscripts. The brotherhood was founded by Maḥammad Ibn Nāṣir, known as Ibn Nāṣir ad-Darʻī (1603–1674), whose son established the central role of Tāmkrūt and can thus be regarded as the founder of this ṭarīqa. He continued the work of his father, and Nāṣiriyya spread fairly quickly across the Maghrib as its followers also created zāwiyas in today’s Tunisia and Algeria. Although Nāṣiriyya’s roots go back as far as the son of Abū Ṭālib, Ǧaʿfar, it is an orthodox Sunni brotherhood that adheres to the Maliki law school, strongly connected to the central authorities of Morocco. The article also presents the figure of Ibn Nāṣir, a widely recognized mystic and theologian, and a Muslim lawyer. His main work is Al-Aǧwiba an-Nāṣiriyya [“An-Nāṣirī’s Response”] a text of predominantly legal character. However, his prayer in verse, known widely as Sayf Ibn Nāṣir [“The Sword of Ibn Nāṣir”] is especially popular. The article also dedicates a few paragraphs to his son, Aḥmad al-Ḫalīfa. Further in the article, an outline is provided concerning the mystical rituals of Nāṣiriyya, originating from the brotherhood’s founder.